Twisters and other terrible storms a nonfiction companion to Twister on Tuesday - Osborne, Will.; Osborne, Mary Pope.; Murdocca, Sal; Osborne, Mary Pope. (New York Random House, 2003)
Describes the changing nature of weather and how meteorologists predict and study such storms as tornadoes, hurricanes, and blizzards.
"A stepping stone book."
Keywords: Severe storms -- Juvenile literature; Tornadoes; Hurricanes; Blizzards; Weather; Meteorology; Meteorological storms, prediction and research